INTEGRITAS, MORALITAS, DAN KEPERCAYAAN PUBLIK DALAM PERSPEKTIF KEBIJAKAN PENGADAAN HAKIM DI INDONESIA - Sheva Krisna Danendra; Titus Perdana Sulistyo; Moch. Ali Mashuri (Universitas Halu Oleo, 2022)
The integrity inherent in a judge is a code of ethics and an absolute thing that must be present in a judge. This can be proven by the implementation of Regulation of the Supreme Court of the Republic of Indonesia Number 2 of 2017 concerning the Procurement of Judges for Case Study Participants who do not pass the Education and Training Program for Integrated Candidates for Judges Batch III. The type of research used in this study is a survey of informants by applying a literature review approach. The results of this discussion indicate that the integrity of a judge is very important because it is closely related to how a judge can uphold justice. Apart from having a soul with integrity, a judge candidate also requires credibility and capability in carrying out his duties and functions as a judge. Therefore, participants who do not pass the education and training program for prospective judges cannot be reappointed as staff or employees in any judicial environment, be it the General Court, Religious Court, State Administrative Court, Military Court, and prospective judges must be dismissed with respect as a person. Government employees.